Pendidikan agama Islam sebagai pembentuk karakter anak - Aisy, Salwatul (Maliki Interdisciplinary Journal, 2024)
Islamic education is a system that focuses on guidance and character development based on Islamic teachings and values. The aim is to form individuals who are civilized, dignified and useful, and can live in peace and prosperity in accordance with Islamic ideals. Character education in Islam is defined as guidance given by adults to children to achieve maturity. Character here includes psychological, moral and personality traits that distinguish a person. Character education aims to instill moral values, good actions and positive personalities in students, so that they can apply them in everyday life. Islamic education involves the important role of family, school and society in shaping children’s personalities. Parents as the first educators have a big responsibility in shaping children’s morals and ethics. Schools complement family education by emphasizing the development of cognitive knowledge and psychomotor skills, while the community provides an environment that supports the development of children’s character through social interaction and the application of Islamic values. Thus, Islamic education does not only focus on imparting knowledge, but also on forming good character and developing individual potential to the maximum to achieve insan kamil, or perfect humans, who have moral and spiritual integrity in accordance with Islamic teachings.